Minimum wage violations in Honduras - Andrés Ham (IZA Journal of Labor & Development, 2015)
This article studies minimum wage non-compliance in Honduras, a dual labor market with high wage floors that are weakly enforced. However, rather than just counting how many workers earn sub-minimum wages, it also estimates violation indices that measure compliance at the intensive margin. I first explore cross-sectional heterogeneity in violations using household survey data. Then, I quantify compliance adjustments to minimum wage hikes by comparing indices before and after a large unexpected increase. Results show substantial differences in non-compliance across industries, location, and coverage status. Violations worsen with rising minima, but less in in more compliant sectors.
Keywords: J38; J42; O54; 330; Minimum wages; Compliance; Violations; Dual labor markets; Honduras